Bateeq packers - Shopit, Nurul Nabilah; Mohd Azami, Nurul Azmina Afifah; Ujang, Rio; Abd Kadir, Nur Athirah; Wee, Hassnah (Universiti Teknologi MARA, Kedah, 2022)
Customers view innovation as crucial to achieving their satisfaction and gratifying their demands. It needs the creation of a novel concept that will be implemented to give businesses a competitive advantage. Those who enjoy travelling must carry bags at all times. Others, however, like to have multiple bags with various necessities. When selecting a travel bag, it is vital to examine the destination, travel pattern, holiday duration, and activities. The luggage size should be appropriate for the trip's and the journey's needs, whether a brief vacation or a week-long excursion. The Bateeq Packers product's features make it simple to use and transport, whether travelling or engaging in outdoor sports. It is ecofriendly and ideal for a variety of tourism industry segments. Due to its low price, it has commercialisation potential. The product would also benefit society by encouraging individuals to recycle plastics. This would make the environment more sustainable and meet the Sustainable Development Goals (SDG) for innovation in industry and infrastructure (SDG9), responsible consumption and production (SDG12), and good health and well-being (SDG3).